A experiência de ser jovem e mulher em uma igreja tradicional protestante - Marinho, Noélia Nunes (2017)
The dissertation seeks to investigate how some young people and women articulate their religious experiences in the church Assembly of God (missions) in Maceió to their youthful experiences, in view of the multiple processes of socialization that occur in addition to that dispensed by this church. In this perspective, conflicts have been identified due to the clash between divergent camps, and in the face of this, a "deviant condition" is built by the production of "formal" and "informal" norms by the church; And as a result of the dynamism in social relations, this condition is shaped by the relationality with which it is perceived in the historical and generational course. In the exercise we propose, the researcher's experience, as a native, was identified by her as a propeller of a better understanding of the dilemmas that specifically live the youths and women in relation to the church and also in the "inside" versus the "outside" "Of hers, since he experienced close up some of these dilemmas, which led to the rupture with the church. A generational theory is considered in this research and, in this sense, for the understanding of the conflicts about the uses and customs between the generations in the church, in order to identify distinct logics on how to dress in a "holy" way, we search in history The church and also through bibliographical and documentary efforts the conditions that have shaped the current logic of action and lifestyle in the face of world dress and perception. In addition, we use a comprehensive sociology to seek the senses dispensed by the members to their actions, and anchored participant observation techniques and semistructured interviews, we intend to make clear what underlies a heterogeneity in the behaviors in front of an idea of tradition in which A "staticity" is desired by the leaders and older members, that is, the detachment and denial of any "new" elements. This attitude contrasts with a youthful behavior that has re-signified the tradition, from an "attractiveness" identified in the field, which at the same time stresses the traditional way of being "assembly", manages to promote a cultural renewal in the church.